The implications of holding a Postgraduate Certificate in Education versus a B.Ed. qualification in finding employment at Bohlabela District, Manyeleti Circuit, Mpumalanga Province, South Africa - Mohammed Xolile Ntshangase; Nkarhi Mathebula; Mbongiseni Michael Buthelezi (Sosio-Didaktika: Social Science Education Journal, 2025)
Educators’ qualifications are of two types in South Africa, while the common one is a 4-year Bachelor of Education (B.Ed) those who already have graduated with other degrees enrol for a 1-year Postgraduate certificate (PGCE) for those who have already graduate with other degrees  . The problem of PGCE teachers is that they are not well grounded in pedagogics like B.Ed ones. This problem gets compounded as the pass-rate declines in schools with more PGCE teachers than B.Ed qualified ones. The purpose of this study is to explore the factors beyond the decline in pass-rate within the schools where there are more PGCE teachers than B.Ed teachers. This study sampled 11 participants comprised of 5 PGCE teachers, 5 B.Ed teachers, and 1 circuit manager from Manyeleti circuit in Mpumalanga province of South Africa, for semi-structured interviews. This study adopts social learning theory, and it marks its contribution to literature by giving some insights on the negativity of preferring one kind of qualification in terms of employment instead of embracing the diversity. Findings entail that PGCE teachers are unreasonably favoured in Mpumalanga province and that contributes to low pass-rate. Then, data will hereby be thematically analysed during this explorative study. Keywords: PGCE; B.Ed; pedagogics; pass-rate; employment